The influence of existence–relatedness–growth need satisfaction and job burnout of young university teachers: the mediating role of job satisfaction - Yang, Yang; Ling, Que (Frontiers in Psychology, 2023)
Job burnout among young university teachers is a serious issue that can have negative consequences for their well-being and job performance, as well as students’ learning outcomes. To identify protective factors for job burnout, this study examined the impacts and mechanism of satisfying existence, relatedness, and growth need on job burnout among 968 young university teachers, using the ERG needs theory framework. The results of the regression analysis and mediation analysis showed that ERG needs satisfaction significantly and negatively predicted job burnout, and job satisfaction mediated this relationship. Besides, the total effect of existence need satisfaction on job burnout was significantly smaller than that of relatedness need satisfaction and growth need satisfaction. These findings contribute to our understanding of the antecedents of young university teachers’ job burnout and provide a theoretical basis for practical action to protect them from burnout by enhancing their need satisfaction and job satisfaction.